Effects of a new early municipality-based versus a geriatric team-based transitional care intervention on readmission and mortality among frail older patients – a randomised controlled trial. (November 2021) - Hansen, Troels Kjærskov; Pedersen, Lene Holst; Shahla, Seham; Damsgaard, Else Marie; Bruun, Jens Meldgaard; Gregersen, Merete
Highlights: Unplanned readmission is a major threat and burden to frail geriatric patients. The best way to manage transitional care for frail geriatric patients is unclear. Two transitional care intervention models were compared in this RCT (n=3, 103). A hospital-based team was superior to a primary care-based, nurse-led intervention. Reduced readmission but no difference in mortality or length of hospital stay. Abstract: Purpose Previous studies reported reduced risk of readmission, mortality and shorter length of hospital stay (LOS) among geriatric patients receiving an early (<24h), hospital-based geriatric team intervention after discharge. The objective of this study was to compare a novel, early municipality-based, nurse-led and general practitioner (GP)-supported transitional care intervention (TCI) to an established hospital-based TCI among frail, older, geriatric patients. Material and methods A randomised controlled trial was conducted within a single geriatric department and the adjacent municipality. Inclusion criteria: acutely admitted, frail patients 75+ years old. Eligible patients were randomly allocated (1:1) to the two TCIs. Primary outcome was 30-day unplanned readmission. Secondary outcomes were 90-day all-cause mortality and LOS. Stratified analysis according to type of dwelling was made. Odds ratios (OR) with 95% confidence intervals (CI), and number needed to treat (NNT) were reported. Results 3, 103 patients (median age (IQR): 85 (80-90); 57% female) were included. Readmission rates were 22% in the municipality-based intervention (n=332/1, 545), and 18% in the hospital-based intervention (n=276/1, 558); OR was 1.27, 95% CI (1.06-1.52), p=0.008 and NNT=27. OR for cohabiting patients was 1.47, 95% CI (1.02-2.08); p=0.035. No significant difference was observed in mortality (22% vs. 21%; OR=1.05, 95% CI (0.89-1.25), p=0.577) or LOS (median (IQR): 6 (2-8) vs. 6 (2-8) days, p=0.1787). Conclusions The new municipality-based, nurse-led and GP-supported intervention was inferior to the hospital-based geriatric team intervention in preventing 30-day readmission among frail, geriatric patients. There was no significant difference between the two interventions in regard to 90-day mortality or LOS.